A compact metamaterial broadband THz absorber consists of graphene crosses with different sizes. (November 2021) - Liu, Wen; Lv, Yisong; Tian, Jinping; Yang, Rongcao
Abstract: A compact tunable graphene-based broadband metamaterial absorber in the terahertz (THz) frequency band was presented in this paper. The proposed absorber is the classic sandwich structure, which is composed of graphene cross resonators of different sizes placed on the top of a dielectric spacer backed with a gold ground at the bottom. It is shown that the absorber can achieve a broad absorption band from 2.81 THz to 4.67 THz with absorption up to 97 % under the normal incident. Meanwhile, the absorption property can be kept to a moderate level when the incident angle is up to 45° for both TE and TM incident light, and the absorption is polarization insensitive. By increasing the chemical potential of graphene from 0.40 eV to 0.60 eV, the broad absorption band can be tuned to shift blue with slightly changing maximum absorption rate. What's more, the absorption bandwidth can be further extended to over 2.34 THz with absorption larger than 97 % by adding another graphene cross layer. Based on the optimal and novel characteristics, we hope that the designed absorber may have potential applications in THz absorbing, sensing, switching, modulating, stealthy and so on. Highlights: The absorber only consists of graphene patterns, dielectric, and gold ground making it easy to be fabricated. Absorption over 97 % can be realized in 2.81–4.67 THz under the normal incident with bandwidth up to 1.86 THz. Absorption property is wide-angle in incidence and is insensitive to the polarization angles. Absorption performance has an obvious improvement than some other reported literatures.